"Adolescents who feel depressed are rejected but do not withdraw: A longitudinal study of ethnically diverse friendship networks in England, Sweden, and Germany". (September 2021) - Aronson, Olov; Bergh, Daniel
Abstract: Adolescents who feel depressed are likely to experience social isolation from friends. Previous studies have put forward at least four hypotheses that can account for the association between felt depression and social isolation. The hypotheses are: (1) adolescents who are rejected tend to feel more depressed, (2) adolescents who feel depressed tend to become rejected, (3) adolescents who withdraw from friends tend to feel more depressed, and (4) adolescents who feel depressed tend to withdraw from friends. The present study aims to test these four hypotheses in ethnically diverse contexts in three countries. Two waves of data from England ( n = 515), Sweden ( n = 1, 228), and Germany ( n = 869) were obtained from the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU). One separate stochastic actor-oriented model of the longitudinal coevolution of friendship networks and felt depression was estimated for each of the three countries using the statistical package RSiena. The results consistently indicated that, in all three countries, adolescents who felt depressed were rejected by their peers. Also, the results consistently indicated that adolescents who felt depressed sought more friends, and the results therefore refuted the suggestion that adolescents who feel depressed withdraw from their friends. The findings of the study can inform health-promotion interventions that attempt to limit the social isolation of adolescents who feel depressed in ethnically diverse contexts. More specifically, the study suggests that the social isolation of adolescents who feel depressed may be limited through interventions that reduce the rejection that these adolescents experience from their peers. Highlights: Adolescents who feel depressed are less often selected as friends. Adolescents who feel depressed select more friends. Interventions to reduce isolation should focus on rejection rather than withdrawal.